Adsorption of nitrate, nitrite, and ammonium ions on carbon adsorbents - Andrzej Gierak; Iwona Łazarska (Adsorption Science & Technology)
This work presents the results of the investigations of the adsorption process of nitrate, nitrite, and ammonium ions on carbon adsorbent with the application of the solid phase extraction method to isolate and enrich the investigated ions from aqueous solutions of the concentration below 1 mg/L. For the determination of the concentration of the analyzed ions, we applied the ion chromatography method. The sorption capacity for the tested adsorbents as well as the efficiency of the enrichment of the investigated ions were determined.